Original articleInterstitial brachytherapy guided intensity modulated radiation therapy (IBGIMRT) in cervical cancer: a dosimetric study - Sharma, Daya Nand; Subramani, V.; Rath, Goura Kisor; Jothybasu, K. S.; Bahl, Amit; Julka, Parmod Kumar; Gopishankar, N. (Journal of Contemporary Brachytherapy, 2009)
Purpose: Interstitial brachytherapy (IBT) is used as an alternative to intracavitary radiotherapy in the management of cervical carcinoma. We have devised a new technique called interstitial brachytherapy guided intensity modulated radiotherapy (IBGIMRT) which can potentially reduce doses to organs at risk (OaRs). It utilizes IMRT planning on the target volume (TV) defined by implantation of IBT needles. This study compares the dosimetry of IBT and IBGIMRT. Material and methods: CT scan images of 18 patients with cervical cancer, who have been already treated by HDR-BT, were used to generate two rival plans, IBT and IBGIMRT, for a prescription dose of 10 Gy. Following dosimetric factors were used for comparison: volume receiving 95% of prescription dose (V95), conformity index (COIN) and external volume index (EI) for target and for OaR, dose received by volume of 1 cm3 (D1cc), 2 cm3 (D2cc), 5 cm3 (D5cc) and also volume receiving 50% and 75% of prescription dose (V50 and V75). Results: The two plans resulted in COIN difference of 49.8% (p < 0.0001) and EI difference of 36.4% (p 0.05). Similar figures for rectum with IBT vs. IBGIMRT were 11.2 Gy vs. 7.02 Gy, 10.5 Gy vs. 6.4 Gy and 9.1 Gy vs. 4.8 Gy respectively (p < 0.01). Conclusions: Our novel technique, IBGIMRT, has shown its dosimetric superiority and therefore needs to be studied in clinical set up.